Design of an Affordable Cross-Platform Monitoring Application Based on a Website Creation Tool and Its Implementation on a CNC Lathe Machine - Muhamad Aditya Royandi; Jui-Pin Hung (Applied Sciences, 2022)
Currently, monitoring applications are being designed to provide comprehensive, flexible access. Monitoring applications are also required to function on several platforms (e.g., desktops and mobile phones). However, designers often have difficulty meeting these needs, owing to a lack of expertise in various fields. Here, we aim to convey a simple concept to achieve this goal. Visualization data on the system can be displayed and updated online using Google Sites, which can be accessed on several platforms. The data were displayed using dynamic image HTML embedded code. They were generated from the URL of an image stored in Google Drive. The image was taken from the monitoring system user interface created with the Windows Forms app and periodically uploaded to Google Drive. Therefore, using this concept, a cross-platform monitoring application (CPMA) can be created in a short time without complicated database processing or subscriptions to paid applications. Additionally, a messaging feature from the user platform was developed to enable messaging features between an operator at the machining site and another user/manager of the CPMA. This concept was applied to revisualize the collected data from the data acquisition system and the results of the predicted parameters from the main user interface through image uploadbased data visualization and to monitor two CNC lathe machines (with different sensors attached) at different locations.